FEMINISME : ANTARA OTORITER DAN OTORITATIF - Endrizal Endrizal (HUMANISMA : Journal of Gender Studies, 2018)
This paper is a philosophical description of women's knowledge. Does gender affect the way and what knowledge will be obtained by someone. If we follow the thesis of historical materialism of Marxism, then the answer is "yes," because a person's position in the relations of production determines the way he knows, and what content he will acquire, and women, in patriarchal society, the disadvantaged position. Then, whether to provide a critical assessment of the way and content of gender-affected knowledge requires a certain universal rationality assessment criterion. If so, how to make that rationality no longer a new force of oppressors, as claimed by postmodern thinkers. Feminism, as a philosophical movement and reflection, must use certain universal rationality and criteria of judgment without falling on totalitarianism on the one hand, or relativism on the other. Feminism must be authoritative without being authoritarian